2005
DOI: 10.1039/b502128f
|View full text |Cite
|
Sign up to set email alerts
|

Global partitioning of NOx sources using satellite observations: Relative roles of fossil fuel combustion, biomass burning and soil emissions

Abstract: We use space-based observations of NO2 columns from the Global Ozone Monitoring Experiment (GOME) to derive monthly top-down NOx emissions for 2000 via inverse modeling with the GEOS-CHEM chemical transport model. Top-down NOx sources are partitioned among fuel combustion (fossil fuel and biofuel), biomass burning and soils by exploiting the spatio-temporal distribution of remotely sensed fires and a priori information on the location of regions dominated by fuel combustion. The top-down inventory is combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
420
5
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(464 citation statements)
references
References 65 publications
19
420
5
6
Order By: Relevance
“…Soil NO x Jaeglé et al [43] have performed top-down (satellite) partitioning among NO x sources, including fuel combustion (fossil fuel and biofuel), biomass burning and soils. These are combined with bottom-up inventories to provide much improved a posteriori inventories of NO x sources and their relative importance.…”
Section: Science Studies Including Special Observationsmentioning
confidence: 99%
“…Soil NO x Jaeglé et al [43] have performed top-down (satellite) partitioning among NO x sources, including fuel combustion (fossil fuel and biofuel), biomass burning and soils. These are combined with bottom-up inventories to provide much improved a posteriori inventories of NO x sources and their relative importance.…”
Section: Science Studies Including Special Observationsmentioning
confidence: 99%
“…But for most of the rural Southeast, observed NO 2 is lower at 1000 LT than at 1330 LT. We hypothesize that the opposite diurnal variation between the observed (0. emissions (dependent on soil temperature) are strongest in the afternoon [Ludwig et al, 2001], and there is evidence that these emissions are significantly underestimated in the model [Jaeglé et al, 2005]. Furthermore, Park et al [2007] found strong biomass burning activity throughout the Southeast and GEOS-Chem does not take into account the diurnal cycle of fires (see next section).…”
Section: Diurnal Variation In No 2 Columns Over Fossil Fuel Source Rementioning
confidence: 99%
“…Data sets of tropospheric NO 2 columns retrieved from the Global Ozone Monitoring Experiment (GOME), the Scanning Imaging Absorption Chartography (SCIAMACHY) and the Ozone Monitoring Experiment (OMI) now span more than 10 years (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) and have been used for trend studies van der A et al, 2006a]. GOME and SCIAMACHY tropospheric NO 2 data has been used to estimate surface emissions of NO x [Martin et al, 2003;Jaeglé et al, 2004Jaeglé et al, , 2005Müller and Stavrakou, 2005;Bertram et al, 2005;Toenges-Schüller et al, 2006;Konovalov et al, 2006;Martin et al, 2006;Kim et al, 2006] and lightning NO x production [Boersma et al, 2005;Beirle et al, 2006;Martin et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…These data have been useful for understanding global (e.g., Martin et al, 2003;Jaegl et al, 2005), regional (e.g., Duncan et al, 2016;Travis et al, 2016) and local air quality (e.g., Zhu et al, 2017) over daily (e.g., Valin et al, 2014;de Foy et al, 2016), seasonal (e.g., Russell et al, 2010), interannual, and decadal time periods (van der et al, 2008;De Smedt et al, 2015). However, the relatively coarse spatial resolutions and single daily observation times have substantially limited these applications, particularly within the air quality management community which needs to be able to distinguish temporal profiles of emissions from different source sectors and identify specific physical processes to justify regulatory decisions.…”
Section: Introductionmentioning
confidence: 99%